PERTANGGUNGJAWABAN KEPALA DESA KARANG TUNGGAL KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA DALAM HAL PENGELOLAAN KEUANGAN DAN ASET DESA (DITINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 6 TAHUN 2014 TENTANG DESA) - Andreas Susanto Marbun; Dinny Wirawan Pratiwie (Yuriska: Jurnal Ilmiah Hukum, 2018)
The Unitary Republic of Indonesia's Republic of Indonesia in organizing the system of government embraces the principle of Decentralization by providing opportunities and freedom to the regions to organize Regional Autonomy. Indonesia is a regional entity consisting of central government and local government, as regulated in the provisions of Article 18 paragraph (1) of the 1945 Constitution which states that the Unitary State of the Republic of Indonesia is divided into provinces and provinces are divided into districts and city, where each province, district, and city have local government, which is regulated by law. The district / municipality government comprises the subdistrict area, and each sub-district has village / village in it, the village's new face becomes the hope of accompanying the establishment of Law No. 6 of 2014 on the Village which becomes the starting point of the village's hope to be able to determine the position, role and authority over himself so that the village can be politically and politically swayed as the foundation of village democracy, as well as economically and culturally dignified as the face of village self-reliance and rural development. Article 26 has given the village chief the opportunity to manage the finances and assets owned by the village. The stages of the village financial management have been regulated by the Minister of Home Affairs Regulation No. 113 of 2014 on Village Financial Management, and the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 1 of 2016 on Village Asset Management regulates the procedures for managing village assets. The management of village finances and assets can’t be separated from the ability of the Village Head and other village apparatus. The responsibility of the Village Head in managing village finances and assets properly, transparently and in accordance with applicable laws and regulations is necessary to promote the development and economy of the village, including Karang Tunggal village as one of government under Kutai Kartanegara.